Modalitas sebagai Realisasi Makna Interpersonal dalam Instagram dr.fitrihartanto_spak “Rahasia Anak Gak Speech Delay!” - Dies Oktavia Dwi Astuti; Asep Purwa Yudo Utomo; Teguh Supriyanto (Jurnal Kajian dan Penelitian Umum, 2026)
This article examines modality as the realization of interpersonal meaning in Instagram content posted on the account dr.fitrihartanto_spak, which focuses on child health and development. The study aims to identify the types of modality used by Dr. dr. Fitri Hartanto, Sp.A(K) in the content entitled “Rahasia Anak Gak Speech Delay!” (“The Secret to Preventing Speech Delay in Children”) and to reveal the speaker’s position in constructing interpersonal relationships with the audience. The data consist of utterances delivered by Dr. dr. Fitri Hartanto to the followers of the Instagram account. The analysis employs the Systemic Functional Linguistics approach, particularly the modality system, which reflects the speaker’s attitude, confidence, and authority toward the conveyed information. The findings indicate that the dominant modalities are high-probability modalization and high-obligation modulation. The use of high-probability modalization demonstrates a strong degree of confidence in the information presented, while high-obligation modulation emphasizes actions that parents should or must undertake to support their children’s language development. These findings suggest that Dr. dr. Fitri Hartanto occupies a higher authority position than the audience, resulting in a non-equal interpersonal relationship in which the speaker is positioned as a trusted source of knowledge and expertise.